Exploring indium-based ternary thiospinel as conceivable high-potential air-cathode for rechargeable Zn-air batteries - Fu, Gengtao (2020)
Reversible oxygen reactions in Zn–air batteries require cost‐effective and highly‐active bifunctional electrocatalysts to substitute traditional noble‐metal based catalysts. Herein, a new and promising electrocatalytic material, ternary CoIn2S4 thiospinel, is demonstrated for effectively catalyzing oxygen reduction and oxygen evolution reactions (ORR and OER) with S‐doped reduced graphene oxide (S‐rGO) as an electronic conductor. Compared with Co9S8/S‐rGO (without In doping), the newly developed CoIn2S4/S‐rGO reveals superior electrocatalytic properties for the ORR (half‐wave potential of 0.83 V) and OER (overpotential of 0.37 V at 10 mA cm−2), demonstrating that the introduction of In can promote the reversible oxygen electrode reactions of CoIn2S4. The superior experimentally‐observed electrocatalytic properties are corroborated via density function theory investigations. Meanwhile, the synergistic improvements in the bifunctional activities resulting from the combination of CoIn2S4 and S‐rGO are also confirmed. As a proof of concept, home‐made Zn–air cells are assembled with CoIn2S4/S‐rGO as an air‐cathode. The developed Zn–air cells exhibit a high peak power density (133 mW cm−2) with an energy density of 951 Wh kgZn−1 and robust cycling stability over 150 cycles for 50 h, exceeding of those commercial Pt/C+RuO2 which highlights the practical viability of CoIn2S4/S‐rGO for rechargeable Zn–air batteries.